The Role of Dormitory Coaches in the Formation of Religious Character of Students at the DDI Galla Raya Islamic Boarding School - Zul Afief Hamdany Abdullah; Herdah; Muh. Akib (Al-Iftah: Journal of Islamic studies and society, 2024)
This study discusses the role of dormitory coaches in the formation of students' religious character. This study aims to analyze the role of coaches in the formation of students' religious character, the character of students in Islamic Boarding Schools and the obstacles faced by coaches in the formation of students' religious characters. This research is a qualitative descriptive research, the type of data uses the type of subject data and the data source is the dormitory coach, then the processing techniques and stages of data collection used are observation, in-depth interviews and documentation. The data analysis includes data reduction, data presentation and conclusion drawing and verification. And the data validity testing techniques used are Credibility, Transferability, Dependability and Confirmability tests. The results of the study show that: 1) Coaches at the DDI Galla Raya Islamic Boarding School play an important role in shaping the character of students through religious, moral, and social guidance. They create a supportive learning environment, teach religious values, and help students deal with emotional problems. The coach also establishes communication with students and parents to ensure that education is in accordance with the values at home. 2) The DDI Galla Raya Islamic Boarding School has succeeded in fostering the character of students through comprehensive religious education. Santri showed positive developments in faith, understanding of Islamic values, as well as attitudes of ihsan, piety, and ethics. They are committed to worship, applying Islamic teachings, and maintaining friendship. Despite the challenges, progress in religious and moral values remains significant.3) Obstacles in instilling religious character in students at the DDI Galla Raya Islamic Boarding School include differences in backgrounds that cause variations in material understanding, mental health problems such as stress, and the negative influence of the dormitory environment exposed to modern technology. In addition, the diversity of students' learning styles makes the same teaching methods not always effective, and the evaluation of the development of religious character often focuses only on theoretical aspects. All these obstacles need to be considered so that students can develop properly in faith and religious practice.